2000
DOI: 10.1002/(sici)1098-2795(200001)55:1<83::aid-mrd11>3.3.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor is expressed in pig embryos during preimplantation development

Abstract: Although estrogen is recognized as essential for embryonic development and maintenance of pregnancy, it remains unclear whether it has a direct role in the embryos themselves. The aim of this study was to investigate whether estrogen can have any effect in pig embryos during preimplantation development. Since the function of estrogen is mediated through its specific receptor, estrogen receptor (ER), the presence of ER mRNA and protein in pig embryos collected in vivo at different stages of preimplantation deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…In contrast, ESR1 occurs mainly in the mammalian uterus (Byers et al, 1997;Couse et al, 1997;Drummond et al, 1999) and it is essential for female sexual differentiation, fertility, and lactation (Drummond et al, 2002). Previous studies showed that the physiological roles of estrogens in the ovary are mediated more by ESR2 than by ESR1 during early postnatal development (Ying et al, 2000;Nilsson et al, 2001;Kowalski et al, 2002;Ni et al, 2007). Therefore, this probably explains why the increase of ESR2 expression from the age of the first egg to 500 days was higher than that of ESR1.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, ESR1 occurs mainly in the mammalian uterus (Byers et al, 1997;Couse et al, 1997;Drummond et al, 1999) and it is essential for female sexual differentiation, fertility, and lactation (Drummond et al, 2002). Previous studies showed that the physiological roles of estrogens in the ovary are mediated more by ESR2 than by ESR1 during early postnatal development (Ying et al, 2000;Nilsson et al, 2001;Kowalski et al, 2002;Ni et al, 2007). Therefore, this probably explains why the increase of ESR2 expression from the age of the first egg to 500 days was higher than that of ESR1.…”
Section: Resultsmentioning
confidence: 99%
“…The same study also demonstrated that resveratrol induced proliferation of various human cell lines by stimulating the estrogen receptor in a dose dependent manner. The estrogen receptor has long been implicated in the regulation of cellular development [35] and its expression was shown in preimplantation pig embryos [36]. In addition, in another report low concentrations (5-10 μM) of resveratrol induced S-phase entry and this pro-proliferation effect was limited to cells possessing androgen receptors [18].…”
Section: Discussionmentioning
confidence: 99%
“…In the developing mouse embryo, ERα, ERβ, and PR are expressed at the blastocyst stage and thereafter [16][17][18][19][20][21][22][23]. The expression of these receptors in mES cells may not directly reflect the same timing as in development, but their expression in mES cells allows us to use it as a model system of in vitro differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Other members of the nuclear receptor family, estrogen receptor alpha (ERα), estrogen receptor beta (ERβ), and progesterone receptor (PR) are present in the early developing embryo of mice and other species [16][17][18][19][20][21][22][23]. In particular, ERα is present in the oocyte, shows variable expression through the morula stage, followed by increased expression in the inner cell mass of the blastocyst.…”
Section: Introductionmentioning
confidence: 99%